2020
DOI: 10.11648/j.aff.20200904.15
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability, Heritability and Genetic Advance Among Bread Wheat Genotypes at Southeastern Ethiopia

Abstract: The knowledge of nature and magnitude of variation existing in available breeding materials is great importance for successful selection of varieties. This study was conducted to generate information on the extent of genetic variability in advanced bread wheat lines. Thirty bread wheat genotypes were tested at Sinana and Agarfa, Southeastern Ethiopia, in alpha lattice design with three replications. Combined over locations ANOVA was carried out for yield and yield related traits. There were highly significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
19
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 8 publications
14
19
1
1
Order By: Relevance
“…High heritability and genetic advance as percent of mean were found in plant height, thousand kernel weight, kernels per spike and grain yield, indicates that most likely the heritability is due to additive gene effects and selection may be effective in early generations for these traits. This finding was agreed with the result of Tilahun et al (2020).…”
Section: Genetic Variability Heritability and Genetic Advancesupporting
confidence: 93%
See 1 more Smart Citation
“…High heritability and genetic advance as percent of mean were found in plant height, thousand kernel weight, kernels per spike and grain yield, indicates that most likely the heritability is due to additive gene effects and selection may be effective in early generations for these traits. This finding was agreed with the result of Tilahun et al (2020).…”
Section: Genetic Variability Heritability and Genetic Advancesupporting
confidence: 93%
“…High genotypic variability (σ 2 g) and Phenotypic variability (σ 2 p) was recorded for number of kernels per spikelet with the value of 146 and 177.3, respectively, while lower values were observed for spike length (1.3 and 2.2) ( Table 2) .Phenotypic variance was higher than genotypic variance for all the yield and yield contributing characters, which indicates the influence of environmental factors on these traits. Tilahun et al (2020) and Alemu et al (2020) also reported that phenotypic variance was higher than genotypic variance for all the yield and yield contributing characters.…”
Section: Genetic Variability Heritability and Genetic Advancementioning
confidence: 93%
“…Through this studied, low GCV and PCV reported by earlier researchers for days to heading, [5,25,36]; days to maturity [5,24,25,36]; grain filling period [5,8,25,36]; and hectoliter weight [5,24,25].…”
Section: Estimations Of Phenotypic and Genotypic Coefficientmentioning
confidence: 77%
“…Previous studies [1,2,24] found very high estimates of broad sense heritability. Previous researchers have reported medium estimates of broad sense heredity for days to heading [14], days to maturity [38], hector liter weight [11,25], and grain yield [5,25,28]. Low estimates of broad sense heritability also reported by previous researchers for grain filling period [1,14,26].…”
Section: Estimation Of Heritability and Genetic Advancementioning
confidence: 98%
“…(2018),Jaur (2019),Khanzada et al (2019),Mishra et al (2019),Shah et al (2019),Al-Naggar et al (2020),Bayisa et al (2020), Ferede and Worede (2020) andNizamani et al (2020).…”
mentioning
confidence: 98%